The justice of Bunny King [videorecording (DVD)] - Henderson, Sophie (Actor); Davis, Essie; McKenzie, Thomasin, 2000-; Nili, Lively; Sisson, Bridie; Tang, Xana (FilmRise, 2023)
Bunny King is a mother of two and a rough-cut diamond with a sketchy past. While battling the system to try and reunite with her children, a confrontation leads Bunny to take her niece Tonyah under her wing. With the world against them both, Bunny's battle has just begun.